Outsourcing in Agriculture in Kazakhstan: Current State and Prospects - A. A. Satybaldin; B. E. Agniyazov; B. S. Myrzalyiev (Экономика: стратегия и практика, 2023)
The article deals with the problems of increasing the efficiency of enterprises of the agro-industrial complex, the feasibility and possibility of using the outsourcing model in the business organization, the advantages of increasing labor efficiency and forms of management using an outsourcing system for agro-industrial structures are studied. In the post-crisis period, the negative results and principles of agribusiness organization were considered as a new direction for ensuring the sustainable development of agriculture by revising the outsourcing service. At the same time, the problem of increasing the efficiency of the economy of the agro-industrial complex of Kazakhstan was formulated, and much attention was paid to the study of the regional direction and the introduction of outsourcing processes. The aim of the study is to analyze the organizational and economic essence of outsourcing and increase the efficiency of agricultural enterprises using this tool in rural business. When studying outsourcing relations in agricultural enterprises, such methods of research methodology as systemic and situational analysis were applied when introducing outsourcing the theory of the synergetic concept, comparative analysis and synthesis, methods of institutional economic analysis and generalization. The results of the study on the development of outsourcing activities are aimed at the use by small and medium-sized agricultural enterprises, market organizations in business restructuring, as well as management bodies of associations, unions, and support centers interested in providing real assistance to rural entrepreneurs.